Spacecraft autonomous navigation using unscented particle filter-based celestial/Doppler information fusion - Ning, Xiaolin; Fang, Jiancheng (Measurement science & technology, 2008)
With the development of space missions, especially manned space missions, a reliable and secure navigation system, and assured autonomous capability in case of emergencies in space, is needed. In order to compensate for the insufficiency of ground station tracking and control, a new autonomous celestial/Doppler-integrated navigation method for a spacecraft is proposed. Celestial navigation is a fully autonomous navigation method, but in some situations the navigation accuracy of this method is subject to the inaccuracies of the measuring devices. Doppler navigation can serve as a good complement to celestial navigation. Because both the state and the measurement models of a celestial/Doppler- integrated navigation system are nonlinear and non-Gaussian, the unscented particle filter (UPF) based information fusion method is proposed here to fuse the position signals from the celestial navigation and Doppler navigation subsystems, and to enhance the navigation accuracy. The performance of this new method is tested and examined using actual spacecraft-orbit data. Simulations show that the position and velocity accuracies are estimated to within 300 m and 0.5 m s-1 respectively, which demonstrate the feasibility and effectiveness of this method. Moreover, it can be used as a backup system to provide redundancy.